The influence of guided inquiry models on students' science processing skills through reflex movement practicum - Yuliana, Lili; Lissa, Lissa; Subkhi, Nur (IAIN Palangka Raya, 2024)
The importance of Science process skills (SPS) in education is that as SPS develops, essential competencies will also improve, including students' scientific attitudes and problem-solving skills. SPS are still rarely assessed because teachers generally measure only cognitive learning outcomes. This research aims to determine the effect of the guided inquiry model on students' science process skills through a reflex movement practicum at SMAN 1 Lohbener. This quantitative research uses a quasi-experimental method with a posttest-only control design. The population of this study consists of XI MIPA, with the sample being class XI MIPA 1 as the experimental group with 16 students and XI MIPA 2 as the control group with 20 students. The instrument used was an essay test sheet on SPS based on five indicators: observing, classifying, predicting, concluding, and communicating (Hastuti & Wiyanto, 2019). The research results showed that the average score for the experimental class was 13,56, while the control class scored 10,95, with a significant level (α) = 0,05, S2gab = 6,48, tcount = 3,06 and t-table = 2,03. Because tcount > table, thus, hypothesis (Ho) is rejected. That means the guided inquiry model affects students' science process skills in the reflex movement practicum at SMAN 1 Lohbener.